AKTIVITAS KESENIAN KOMUNITAS SARANG TARUNG - Hidayah, Fajar Nurul (Institut Seni Indoensia Surakarta, 2017)
This article is the result of research that discusses the Sarang Tarung community art activities. The focus of the problem under study is the meaning that encourages the Sarang Tarung community to perform art activities, also discusses the background of the community's establishment, and how their activities are. The research method used is ethnography with taxonomic analysis. Symbolic interactionism theory (Herbert Blumer) is used as a scalpel. Sarang Tarung seen through symbolic interactionism is a series of processes of formation of meaning that underlie them to carry out artistic activities. Through symbolic interactionism, it can be seen that the meaning of art activities for the Sarang Tarung community is a form of caring, and it can be seen that the Sarang Tarung community does not fully understand popular art, they are also part of young people who consume popular art trends. They assume that popular art is a form of solidarity that is capable of giving changes to the welfare of the lower classes. This assumption encourages them to carry out artistic activities and not just become passive consumers.Â Keywords: Art Activity, Symbolic Interactionism, Sarang Tarung Community, Meaning.Â